A história (avaliada) em tela : o uso dos filmes no Exame Nacional do Ensino Médio na perspectiva da disciplina de História - Gama Neto, Estefanio José da (2018)
The dissertation investigated how the movie are worked on question of the ENEM - National Examination of Middle Education - in the perspective of the history subject, knowing that the ENEM it’s the main Evaluation instrument of the young people from middle education graduates, and it´s the biggest selection process of applying for public high education. A brief analysis was accomplished about the authors who approach the film as historical document, and also analyzed official documents like the law LDB, the PCNs and the recent and contested BNCC. As an indispensable tool for the questions’ lifting from ENEM, it was used the on line platform called super teacher that has a questions' database of all editions and versions of this exam. It was found that of the more than 20 editions of ENEM, there are few questions that use movie as a didactic resource, historical source or narrative, and these questions are based on the pedagogy of skills, and not in the epistemology of historical science.